Encyonema droseraphilum sp. nov. (Bacillariophyta) and other rare diatoms from undisturbed floating-mat fens in the northern Rocky Mountains, USA - Bahls, Loren; Pierce, John; Apfelbeck, Randy; Olsen, Lois (Phytotaxa, 2013)
Relict assemblages of arctic, sub-arctic, and boreal diatoms were found intact in two undisturbed floating-mat fens at 47o north latitude and 1,830 m elevation in the Rocky Mountains of western Montana, USA. The fens support Encyonema droseraphilum sp. nov. and several rare northern/alpine diatom species—including eleven apparent first records for the contiguous United States—and three species of vascular plants that are imperiled in Montana. For many of the diatoms and one of the vascular plants, the fens are at the southern limit of their known distributions in North America. Twenty-seven of the 49 diatom taxa in the fens are considered at risk or declining in Germany, and similar ratings appear to be appropriate for these taxa in Montana, especially in light of global warming and human destruction of wetlands. A nearby wetland that has been disturbed by dam-building activities of beaver (Castor canadensis), but not by human landscape alterations, produced a diatom assemblage that contained three times more taxa than the fens but was dominated by common species, primarily Staurosirella pinnata. Our findings illustrate the effects of natural, intermediate disturbance on diatom species composition and underscore the importance of protecting undisturbed aquatic systems for the purpose of conserving rare species and for monitoring environmental change.